PENGARUH JENIS DAN WAKTU PERENDAMAN EKSTRAK NABATI TERHADAP INVIGORASI BENIH CABAI KADALUARSA - Redy Gaswanto; Nurmalita Waluyo; Astiti Rahayu; Isum Isum (UIN Sunan Gunung Djati Bandung, 2023)
The expired status is addressed to the seeds that have exceeded the recommended planting period by the producer, while invigoration is the improving process of a vigor or performance of the deterioration seeds. The research purposes were to find out the best composition of kind and immersion time of a flora material extract that could improve physiological quality of the expired chili seeds. The research was conducted at the Seed Laboratory of Indonesian Vegetable Research Institute (IVEGRI), Lembang from Mei 2018 to December 2018 using a Completely Randomized Design (CRD) of 11 treatments which was repeated three times. The treatments consisted of: (1) Control (expired seeds without treatment); (2) Green coconut water 15% + Incubation 24 hours; (3) Ambon banana extract 15% + Incubation 24 hours; (4) Ambon banana extract 15% + Green coconut water 15% + Incubation 24 hours; (5) Cucumber extract 15% + Incubation 24 hours; (6) Green coconut water 15% + Incubation 48 hours; (7) Ambon banana extract 15% + Incubation 48 hours; (8) Ambon banana extract 15% + Green coconut water 15% + Incubation 48 hours; (9) Cucumber extract 15% + Incubation 48 hours; (10) Green coconut water 15% + Incubation 72 hours; (11) Ambon banana extract 15% + Incubation 72 hours. Then, the incubated seeds were germinated using top of paper (TP) method by the Copenhagen Tank apparatus. The results showed that the use of green coconut water 15% + incubation 24 hours (treatment No. 2) or cucumber extract 15% + incubation 48 hours (treatment No. 9) could improve viability and germination speed performance in range 12.67-13.33% and 3.85-5.10%/etmal respectively of the expired chili seeds with viability condition less than 75.00%.